Analisis Normatif Hak-Hak Warga Binaan Dalam Sistem Pemasyarakatan Indonesia: Tinjauan Terhadap Undang-Undang Nomor 22 Tahun 2022 Dan Prinsip-Prinsip Hukum Pidana - Arsyanika Nhayla Ananda; Amelia Saputri; Ganefi (GLOBAL SCIENTS PUBLISHER, 2025)
This study examines the provisions on prisoners' rights in Law Number 22 of 2022 concerning Corrections and their compliance with the principles of criminal law, namely proportionality, human dignity, and the rule of law. The research background stems from various correctional problems in Indonesia, such as overcrowding, violence, discrimination, and lack of access to basic services, which often result in violations of prisoners' rights. This study uses normative legal methods by examining statutory regulations, criminal law principles, and correctional theory. The results show that Law Number 22 of 2022 regulates prisoners' rights more comprehensively through Articles 9 and 10, covering basic rights and integration rights, with the aim of supporting rehabilitation and social reintegration. Furthermore, the provisions in the law align with the principle of proportionality through measurable rights restrictions, the principle of human dignity through guarantees of humane treatment and prohibitions on violence, and the principle of the rule of law through clear legal procedures and oversight mechanisms. However, the implementation of the regulations still faces structural challenges in the field, necessitating the need for comprehensive strengthening of the correctional system